Pengaruh Stres Kerja, Lingkungan Kerja dan Disiplin Kerja terhadap Produktivitas Kerja Karyawan (di PT.Megasari Makmur 1 Bagian Produksi) - Sefta Ariansah; Sri Wahyuningsih (Departement of Mathematics Education, 2023)
This study aims to determine whether there is an influence of Work Stress (X1), Work Environment (X2) and Work Discipline (X3) to influence Employee Productivity (Y) in the Production Department of PT. Megasari Makmur 1. The type of research used is the quantitative method, Approach The research used in this study is descriptive analysis using questionnaire data on 80 respondents from a total population of 80 employees in the production division of PT. Megasari Makmur 1. The sampling technique used is nonprobability sampling with saturated sample method. Test results Test t (correlation significance) using the LISREL application version 8.80.